O&S Voices, Visions, and Values in 100 Published Issues - Paes Barreto Davel, Eduardo (Organizações & Sociedade, 2022)
Readers, reviewers, authors, editors, directors, managers, coordinators, and board members of the O&S are diverse voices that expressed themselves about the importance of the journal. From this variety of voices, we identified visions and values that highlight five points of identity of the journal: (a) a consolidated journal that dares, innovates, and renews itself, (b) a relevant journal that seeks excellence, rigor, and social commitment, (c) an open journal that includes the diverse, the plural, and the silenced, (d) a critical journal that resists, debates, and challenges, and (e) a welcoming journal that promotes engagement, the community, and affection. These are points of identity that, rather than crystallizing or affirming, aim, above all, to inspire a reflection on the past, present, and future of the journal.